The right to education at the heart of the construction of the rule of law in Africa : what prospects for the development of French-speaking African states? - (:unkn) unknown (My University, 2024)
The right to education enshrined in article 26 of the Universal Declaration of Human Rights, the International Convention on the Rights of the Child, the African Charter on the Rights and Welfare of the Child and many other international legal instruments has yet to be effectively implemented. Despite all possible guarantees, not to mention the ongoing efforts of the United Nations, through UNESCO and UNICEF, the right to education is still not an absolute reality throughout the world. Thus, the effectiveness of this right, in Francophone Africa, remains confronted in time by events or situations that contradict the entire expression of its essence. There are several reasons for this, ranging from political and economic factors to socio-cultural constraints. However, in the year 2000, the United Nations had set itself as a concern, through the Millennium Development Goals (MDGs), to succeed in making universal primary education effective. Indeed, consideration of the vital interests of the human being, in other words the defence of human rights, is proving to be the royal road to development. One of these rights is the right to education and training of citizens, which is essential for the construction and promotion of a democratic State governed by the rule of law. In other words, the construction of the rule of law through the prerogatives accorded to education would be a sine qua non for the development process of Francophone Africa. The objective of this thesis is to analyse the close relationship between development, the rule of law and the right to education, while addressing internal and external causes. Our study will therefore have the merit of demonstrating that in a context of building the rule of law in French-speaking Africa, the right to education should be understood as a prerequisite for development.
Keywords: African Research